Medication details documented on hospital discharge: cross-sectional observational study of factors associated with medication non-reconciliation - Grimes, Tamasine C (Blackwell Science Inc, 2011)
AIMS: Movement into or out of hospital is a vulnerable period for medication safety. Reconciling the medication a patient is using before admission with the medication prescribed on discharge, and documenting any changes (medication reconciliation) is recommended to improve safety. The aims of the study were to investigate the factors contributing to medication reconciliation on discharge, and identify the prevalence of non-reconciliation. METHODS: The study was a cross-sectional, observational survey using consecutive discharges from purposively selected services in two acute public hospitals in Ireland. Medication reconciliation, potential for harm and unplanned re-admission were investigated. RESULTS: Medication non-reconciliation was identified in 50% of 1245 inpatient episodes, involving 16% of 9569 medications. The majority of non-reconciled episodes had potential to result in moderate (63%) or severe (2%) harm. Handwritten rather than computerized discharges (adjusted odds ratio (adjusted OR) 1.60, 95% CI 1.11, 2.99), increasing number of medications (adjusted OR 1.26, 95% CI 1.21, 1.31) or chronic illness (adjusted OR 2.08, 95% CI 1.33, 3.24) were associated with non-reconciliation. Omission of endocrine, central nervous system and nutrition and blood drugs was more likely on discharge, whilst omission on admission and throughout inpatient care, without documentation, was more likely for obstetric, gynaecology and urinary tract (OGU) or respiratory drugs. Documentation in the discharge communication that medication was intentionally stopped during inpatient care was less likely for cardiovascular, musculoskeletal and OGU drugs. Errors involving the dose were most likely for respiratory drugs. CONCLUSIONS: The findings inform strategies to facilitate medication reconciliation on discharge from acute hospital care.